Effect of the exosome-mediated suppression of the estrogen signaling: the role in the progression of the hormonal resistance of breast cancer cells - D. V. Sorokin; O. E. Andreeva; E. I. Mikhaevich; Yu. Yu. Shchegolev; A. M. Scherbakov; M. V. Gudkova; M. A. Krasil’nikov (Успехи молекулярной онкологии, 2020)
The most effective treatment of the hormone-dependent breast cancer is based on the antiestrogens SERM and aromatase inhibitor treatment, however its efficiency is limited by the acquired resistance to the drugs.Previously we have revealed the effect of the transferring of the hormonal resistance from the resistant to the sensitive cells under in vitro cell co-cultivation, and demonstrated exosomes involvement in this process. Here we have shown that the exosomes of the resistant cells caused the marked inhibition of the estrogen signaling in the recipient cells, and identified microRNAs – ERα suppressors that overexpressed in the resistant exosomes.Taken together, the results obtained demonstrate the important role of the estrogen signaling suppression in the exosome-induced transferring of the hormonal resistance, and revealed the involvement of the exosomal microRNA in the ERα down-regulation.